2015
DOI: 10.3346/jkms.2015.30.10.1375
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylases and Their Regulatory MicroRNAs in Hepatocarcinogenesis

Abstract: A growing body of evidence suggests that epigenetic modifications are promising potential mechanisms in cancer research. Among the molecules that mediate epigenetic mechanisms, histone deacetylases (HDACs) are critical regulators of gene expression that promote formation of heterochromatin by deacetylating histone and non-histone proteins. Aberrant regulation of HDACs contributes to malignant transformation and progression in a wide variety of human cancers, including hepatocellular carcinoma (HCC), gastric ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“… 108 The mechanisms underlying the dysregulation of HDAC expression in HCC are not fully understood, but a relevant role for specific miRNAs is clearly being elucidated. 105 , 109 A plethora of mechanistic studies have demonstrated the involvement of HDACs in the pathogenesis of HCC. When overexpressed, these epigenetic modifiers display multifaceted pro-oncogenic effects, including the inhibition of TSG expression, activation of cell cycle progression, apoptosis evasion, adaptation to hypoxia and metabolic reprogramming.…”
Section: Epigenetic Alterations In Hepatocarcinogenesismentioning
confidence: 99%
“… 108 The mechanisms underlying the dysregulation of HDAC expression in HCC are not fully understood, but a relevant role for specific miRNAs is clearly being elucidated. 105 , 109 A plethora of mechanistic studies have demonstrated the involvement of HDACs in the pathogenesis of HCC. When overexpressed, these epigenetic modifiers display multifaceted pro-oncogenic effects, including the inhibition of TSG expression, activation of cell cycle progression, apoptosis evasion, adaptation to hypoxia and metabolic reprogramming.…”
Section: Epigenetic Alterations In Hepatocarcinogenesismentioning
confidence: 99%
“…Since HDAC2 deregulation affects cell proliferation, apoptosis, and immune system in AML, focusing on specific miRNAs altered by this epigenetic regulator may identify potential markers for determining the best strategies in AML treatment. To date, many miRNAs were found directly targeted by HDAC2 in several cancers such as colorectal cancer , hepatocellular carcinoma , breast cancer , and AML . In AML, differentially expressed miRNAs have a prognostic and functional role associated with cytogenetics, molecular features, molecular markers, morphology, and clinical outcome .…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of miRNAs is known to facilitate cancer development by upregulating oncogenes or silencing tumor suppressor genes . MiRNAs are transcribed by RNA polymerase II as part of capped and polyadenylated primary transcripts (pri‐miRNAs) that can be either protein‐coding or non‐coding.…”
Section: Discussionmentioning
confidence: 99%